Adolescents with emotional and behavioural problems are at higher risk to become excessive or addicted Internet users: is this association moderated by gender? - Urbanova, Laura Bitto; Holubcikova, Jana; Geckova, Andrea Madarasova; van Dijk, Jitse P.; Reijneveld, Sijmen A. (European Journal of Public Health, 2024)
Background: The Internet offers many opportunities for adolescents to facilitate their lives. However, its everyday use may lead to excessive behaviour, including addiction. Our aim was to assess the association between emotional and behavioural problems (EBP) and level of internet use, and whether gender moderates this association. Methods: We used data from a representative sample of 5,433 Slovak adolescents (mean age: 13.51, 48.8% boys) from the Health Behaviour in School-aged Children-study conducted in 2018, collected through online self-report questionnaires. EBP was measured by the Strengths and Difficulties Questionnaire and excessive internet use (EIU) and internet addiction (IA) by the Excessive internet use scale. We analysed using multinomial logistic regression. Results: More than 25% of the adolescents reported EIU; almost 4% reported being addicted to Internet. EIU was more prevalent in girls, but IA was more prevalent in boys. Adolescents with borderline or increased levels of EBP were more likely to report EIU (odds ratio, OR/95% confidence interval, CI: 1.85/1.60-2.14; 3.16/2.67-3.75, respectively) and IA (OR/95% CI: 2.23/1.57-3.18; 4.89/3.41-7.03, respectively). Adjustment for gender, age or perceived family wealth hardly changed the findings. Moreover, gender did not modify the associations between EBP with EIU. Conclusion: Adolescents with higher levels of EBP are more likely to become excessive Internet users or Internet addicts. This shows a need of early identification of adolescents with EBP as they seem to be relatively vulnerable to develop EIU or IA.